Performance Optimization of Unit 1 General Criminal Actions of Sukoharjo Polres Criminal Reserse in Handling Criminal Acts Through Restorative Justice - Rajendra, Jodaenis (Advances in Police Science Research Journal, 2020)
The development of the criminal justice system in Indonesia has always experienced changing dynamics, especially in alternative settlements of criminal acts from Restorative Justiceto restorative justice, the idea of Restorative Justicehas been known since the 1970s which at that time appeared in Ontario, Canada related to the case vandalism which later became the initial turning point for the development of Restorative Justicein the world, which was demonstrated by several policies by international organizations such as NOVA, and the United Nations. So that in Indonesia, alternatives to solving crimes have begun to appear through Restorative Justicewith the dynamics of an increasing number of cases which have resulted in many pros and cons of settlements related to several things such as the age of the suspect and other material losses. Restorative Justiceby Tito Karnavian then in 2021 it will be included in one of the priority programs of the Chief of Police which in 2021 will issue Perpol No. 8 of 2021 concerning restorative justice, this will also be carried out in the jurisdiction of the Sukoharjo Police which is carried out by the Criminal Investigation Unit, especially Unit 1 Tindak Pidana Umum of the Sukoharjo Police The purpose of this research is to identify problems related to the performance of unit 1 Tindak Pidana Umum satreskrim Polres Sukoharjo in handling criminal acts through restorative justice. This research is a qualitative research using data collection methods in the form of interviews, observations, and document processing to informants in the jurisdiction of the Sukoharjo Police. organizational resources and systems & methods of handling the case.